2018
DOI: 10.3346/jkms.2018.33.e310
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Acute Pyelonephritis in Korea, 2010–2014: Population-based Study

Abstract: BackgroundAcute pyelonephritis (APN) is one of the most common community-acquired bacterial infections. Recent increases of antimicrobial resistance in urinary pathogens might have changed the other epidemiologic characteristics of APN. The objective of this study was to describe the current epidemiology of APN in Korea, using the entire population.MethodsFrom the claims database of the Health Insurance Review and Assessment Service in Korea, the patients with International Classification of Diseases, 10th Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
1
14
2
Order By: Relevance
“…As time goes by, the characteristics of disease change. According to recent studies about APN in South Korea using the claim database from 2010 to 2014, the annual incidence rate was on the increase year upon year and prescription of broad-spectrum antibiotics for the treatment of APN had increased [ 10 , 11 ]. In the present study, we identified the change in characteristics of CA-APN in South Korea from the clinical aspect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As time goes by, the characteristics of disease change. According to recent studies about APN in South Korea using the claim database from 2010 to 2014, the annual incidence rate was on the increase year upon year and prescription of broad-spectrum antibiotics for the treatment of APN had increased [ 10 , 11 ]. In the present study, we identified the change in characteristics of CA-APN in South Korea from the clinical aspect.…”
Section: Discussionmentioning
confidence: 99%
“…As known, South Korea has been experiencing rapid aging and is expected to become one of the most aged countries in the world [ 9 ]. Furthermore, entry barriers to the hospitals have decreased due to the improvement of the social welfare system and the rapid expansion of private medical insurance in the last decade [ 10 ]. Accordingly, we could find that the epidemiologic characteristics of APN, such as the incidence and medical cost, as well as antibiotic prescription patterns for the treatment of APN, have changed in South Korea [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 A Korean study reported that the annual incidence rate of APN per 10,000 individuals has been increasing every year. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Acute pyelonephritis (APN) is one of the most common community-acquired bacterial infections, which usually require antibiotic treatment [1]. The annual incidence rate of APN is 39.1 per 10,000 adults in Korea (9.6 per 10,000 adults for inpatients; 29.4 per 10,000 adults for outpatients), and eleven times more women are diagnosed with APN than men [2]. Enterobacteriaceae are common uropathogen, and Escherichia coli is the most common among them.…”
Section: Introductionmentioning
confidence: 99%